Analisis Pengaruh Volume Kendaraan Terhadap Kualitas Udara di Jalan Pamularsih Semarang - Kamal Rijal Sadewo; Lintang Jata Angghita; R. Clarrino Adesetya (Jurnal Serambi Engineering, 2024)
Pamularsih Street is an alternative road that people use to get to the centre of Semarang City. Pamularsih Street, section KLB 1 - KLB 1+200, is the centre of community activities such as offices, education, commercial and residential areas. Community activities on the highway have the potential to cause air pollution. This research aims to find out whether the volume of vehicles can affect the air quality on Pamularsih Street. The purposive sampling method was used to determine the data collection point, namely the middle of the section KLB 1 - KLB 1+200. Data collection was carried out for 3 days (Monday, Saturday, Sunday). The collection times were morning, afternoon and evening. Quantitative methods are used in data processing with 2 analysis models. The analysis is in the form of anova and linear regression. The results of the research on Pamularsih Street show that the volume of vehicles or the degree of saturation has a correlation and influence on the ambient air quality with a positive correlation between the variables. Apart from this, it can be seen from this research that the air index of Jalan Pamularsih is classified as unhealthy to very unhealthy.